2021
DOI: 10.3389/fimmu.2021.792522
|View full text |Cite
|
Sign up to set email alerts
|

The “Dialogue” Between Central and Peripheral Immunity After Ischemic Stroke: Focus on Spleen

Abstract: The immune response generated by the body after the incidence of ischemic stroke, runs through the comprehensive process of aftermath. During this process of ischemic stroke, the central neuroinflammation and peripheral immune response seriously affect the prognosis of patients, which has been the focus of research in recent years. As this research scenario progressed, the “dialogue” between central nervous inflammation and peripheral immune response after ischemic stroke has become more closely related. It’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
(104 reference statements)
0
12
0
1
Order By: Relevance
“…The data, however, showed here that there was no association between SV and PSD status, but lower SA was significantly associated with PSD status in the presence of CRP rs2794520 C/T genotype and rs1205 C/T genotype. The mechanisms underlying the associations may be that owing to the contribution of CRP polymorphism and CRP levels to immuno-inflammatory process ( 32 , 37 ), patients with the C/T genotypes of rs2794520 and rs1205 may be in a more active inflammatory state so that immune cells and cytokines produced abundantly in the spleen, in response to brain vascular damage, were released into the bloodstream and migrated to the site of brain insult ( 17 , 20 ), aggravating secondary brain inflammatory response which influences serotonin metabolism and causes noradrenergic system and HPA axis imbalance, may culminate in PSD ( 6 , 42 ). There in addition were evidence from animal studies for the involvement of pro- and anti-inflammatory cytokines produced by splenic cells in the formation of depression like behavior ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data, however, showed here that there was no association between SV and PSD status, but lower SA was significantly associated with PSD status in the presence of CRP rs2794520 C/T genotype and rs1205 C/T genotype. The mechanisms underlying the associations may be that owing to the contribution of CRP polymorphism and CRP levels to immuno-inflammatory process ( 32 , 37 ), patients with the C/T genotypes of rs2794520 and rs1205 may be in a more active inflammatory state so that immune cells and cytokines produced abundantly in the spleen, in response to brain vascular damage, were released into the bloodstream and migrated to the site of brain insult ( 17 , 20 ), aggravating secondary brain inflammatory response which influences serotonin metabolism and causes noradrenergic system and HPA axis imbalance, may culminate in PSD ( 6 , 42 ). There in addition were evidence from animal studies for the involvement of pro- and anti-inflammatory cytokines produced by splenic cells in the formation of depression like behavior ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that activation of peripheral immunity and secondary intracerebral neuroinflammation after stroke are mainly the result of brain-spleen communication (16)(17)(18). The spleen is a major lymph organ containing an abundance of immunological cells, which can rapidly deploy the distribution of immune cells in the system to fight injury including brain insult (19).…”
Section: Introductionmentioning
confidence: 99%
“…The number of peripheral lymphocytes decreases exponentially for up to seven days following AIS, with the lowest level occurring after 12 hours [ 8 ]. This dramatic decrease is caused by activation of the hypothalamus-pituitary axis and sympathetic nervous system [ 34 ]. Although the specific molecular mechanism has yet to be elucidated, studies have indicated that one of the DAMPs, HMGB-1, plays an important role during the process of immunosuppression following AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike DNA methylation, histone modification exclusively occurs at the amino-terminal tail protruding out of the histone subunit and is a short-term reversible modification. The amino-terminal tails are subjected to post-translational modification namely methylation, acetylation, phosphorylation, and ubiquitination ( Yu et al, 2021 ). Post-translational modification of amino-terminal tails is associated with DNA repair, activation or repression of gene expression, telomere integrity, and the total interaction changes in response to these modifications are determined by “histone code” ( Ng et al, 2018 ).…”
Section: Histone Modificationmentioning
confidence: 99%